The demographic explosion – risks as well as ethical and legal dilemmas - Klimska, Agnieszka; Kaniewska, Małgorzata (Studia Ecologiae et Bioethicae, 2015)
The article considers risks as well as ethical and legal dilemmas arising from the human population explosion. It presents the causes of this occurrence, its course, and forecasts as to the further growth of the global population. Furthermore, it contains an analysis of birth control methods and shows a link between arguments of selected stances and inter alia economics and ecology. The human population explosion has been recognized by the authors as one of the major causes of the deepening crisis in the natural environmental balance.